Níveis de lisina digestível e de ractopamina para suínos machos imunocastrados em terminação - Bruno Oliver Rosa (2011)
Aiming to evaluate the digestible lysine requirement and ractopamine on performance and carcass characteristics of male pigs immunocastrated in the finishing phase for 21 days. A total of 240 male pigs immunocastrated commercial hybrids derived from strains genetically selected for lean gain, initial weight of 97.72 ± 2.11 kg and final weight of 124.06 ± 4.12 kg. The experimental design was randomized blocks in a factorial 3 x 4, four lysine levels (0.65, 0.80, 0.95, 1.10%) and three levels of RAC (0, 5 and 10 ppm) with four replications and five animals each. For performance measures, no interaction. Supplementation of diets with ractopamine at 10 ppm improves the performance of finishing pigs immunocastrated males from 97 to 124 kg. The level of 0.65% digestible lysine, corresponding to a digestible lysine intake of 23.36 g / day, meets the requirements of these animals. For the ultrasound measurements of carcass characteristics in vivo, no interaction. No significant effect was observed for all traits except on the variable depth of loin, rate of lean gain to levels of RAC and backfat thickness at P2, which showed a linear (P <0.05) for levels of lysine. For the ultrasound measurements of carcass characteristics post mortem, no interaction. No significant effect was observed for all traits except on the variable in P2 backfat thickness, which showed a quadratic effect (P <0.05) for levels of lysine. For the cut yields, observed effect (P <0.05) on the variables of carcass, meat in ham, meat palette between levels of RAC. We conclude that the digestible lysine requirement for pigs immunocastrated males, from 97 to 124 kg, within 21 days, is 0.65% digestible lysine, corresponding to a daily intake of lysine of 23.36 g / day where the lowest level met the requirements. Ractopamine supplementation regardless of the level that was used (5 or 10 ppm) in the diet of male immunocastrated finishing, provides better animal performance, it promotes an increase in final weight, average daily gain, improved feed conversion. Carcass characteristics of RAC supplementation increases the rate of lean gain per day, increasing loin depth and backfat thickness reduction at point P2. The RAC supplementation increases the yield of chilled carcass yield, meat on the shank, beef loin and palette. So pigs supplemented with 5 or 10 ppm RAC, show an increase in the demand of daily digestible lysine intake not exceeding 12.27%.